Considerations for Integrating Advance Care Planning Into the Electronic Health Record: A Primer for Clinicians. (December 2020) - Moses, Adam; Dharod, Ajay; Williamson, Jeff; Pajewski, Nicholas M.; Tuerff, Daniel; Guo, Jia; Gabbard, Jennifer
Opportunities for expanding advance care planning (ACP) throughout the health-care system make it critical that primary care (PC) providers have a basic understanding of how the electronic health record (EHR) can aid promoting ACP discussions and documentation. This article will offer PC providers 5 useful tips for implementing ACP in outpatient settings utilizing the EHR.